A Matter of Attitude: On Responsibility and Self-Critique of Design at Michael Erlhoff (KULT_online, 2022)
Michael Erlhoff reflects on the downsides of design in Im Schatten von Design: Zur dunklen Seite von Gestaltung. He points out in which sectors design evades responsibility and does not assume self-criticism. In six chapters with a broad variety of shorter essays, design and designed services are analyzed and contextualized regarding manipulation, counterfeiting, ethics, moral, humanity, self-disassembly and honesty. The author questions the universality of formal principles such as function, ergonomics, and efficiency and exposes thereby the challenges and limits of design.